Tempering and enabling ambition: how equity is considered in domestic processes preparing NDCs - Holz, C; Cunliffe, G; Mbeva, K; Pauw, PW; Winkler, H (Springer Nature, 2023)
The considerations of how Nationally Determined Contributions (NDCs) to global climate action under the Paris Agreement are ambitious and fair, or equitable, is expected to guide countries’ decisions with regards to the ambition and priorities of those contributions. This article investigates the equity aspect of the NDCs of four cases (Canada, the EU, Kenya, and South Africa) utilizing a combination of document analysis and expert interviews. It interrogates both the NDC documents themselves and, uniquely, the role of international and domestic equity considerations within the domestic policy processes that led to the formulation of the NDCs. For this, 30 participants and close observers of these processes were interviewed. We find countervailing effects of equity on ambition, with an enabling, or ambition-enhancing, effect resulting from international equity, in that these four Parties show willingness to do more if others do, too. In contrast, tempering effect appears to result from domestic equity concerns, for example with regards to real, perceived, or anticipated adverse distributional impacts of climate action across regions, sectors, and/or societal strata. Political cultures differ across the four case studies, as do the key actors that influence domestic policies and the preparations of NDCs. This paper also demonstrates that research on equity in NDCs can benefit from expanding its scope from the contents of NDC submissions to also examine the underlying decision-making processes, to generate insights that can contribute to future NDCs being both equitable and ambitious.